Contraceptive patterns among sub-Saharan African migrant women in France - (:unkn) unknown (My University, 2018)
For immigrant women from sub-Saharan Africa, arriving in France may be a break in their sexual, emotional and reproductive trajectory. If many have already experienced pregnancy before arriving, a number will not have started their reproductive life. However, for women who wish so, the arrival in France and the change in the contraceptive landscape may be an opportunity to access effective contraception or to change the method. In 2010, in France, of the entire population of women between the ages of 15-49 and in need of contraception, 78.5% reported using medical contraception compared to 22.9% in sub-Saharan Africa (all countries combined) for women in the same age group. Moreover, the population from sub-Saharan Africa is particularly affected by HIV/AIDS in Africa but also in France, where they represent the second most affected group.Based on two surveys, Parcours and Vespa 2, our study aimed to highlight the contraceptive practices and possible inequalities in contraception that immigrant women from sub-Saharan Africa face, in order to identify improvements in their sexual and reproductive health care.The results of this thesis highlight that African immigrant women seize a system that articulates the sponsoring of contraception, easier access and medical practices resulting in a strong adherence to effective medical contraception since the majority of women report using the pill, the implant and sometimes the IUD. These results must however be adjusted for two reasons. On one hand, women living with HIV (immigrant women or women born in France) use condoms for the most part. On the other hand, the use of an implant is much more pervasive than in the general population which should encourage us to continue studying to what extent the methods in use correspond to a choice and are adapted to the needs of women.
Keywords: African Research